The effect of exposure to nanoparticles and nanomaterials on the mammalian epigenome - Sierra MI (Dove Medical Press, 2016)
MI Sierra,1 A Valdés,2 AF Fernández,1 R Torrecillas,2 MF Fraga2 1Cancer Epigenetics Laboratory, Institute of Oncology of Asturias (IUOPA), Hospital Universitario Central de Asturias (HUCA), Universidad de Oviedo, Oviedo, 2Nanomaterials and Nanotechnology Research Center (CINN-CSIC), Universidad de Oviedo-Principado de Asturias, El Entrego, Spain Abstract: Human exposure to nanomaterials and nanoparticles is increasing rapidly, but their effects on human health are still largely unknown. Epigenetic modifications are attracting ever more interest as possible underlying molecular mechanisms of gene–environment interactions, highlighting them as potential molecular targets following exposure to nanomaterials and nanoparticles. Interestingly, recent research has identified changes in DNA methylation, histone post-translational modifications, and noncoding RNAs in mammalian cells exposed to nanomaterials and nanoparticles. However, the challenge for the future will be to determine the molecular pathways driving these epigenetic alterations, the possible functional consequences, and the potential effects on health. Keywords: noncoding RNAs, ncRNAs, DNA methylation, histone modification, epigenetics